The role of early maladaptive schemas and difficulties in emotion regulation in the prediction of Gender Dysphoria in Transsexual men - Somaye Rahimi; Mehrdad Kalantari; Mohammad Reza Abedi; Seyed Morteza Modares Gharavi (روانشناسی و روانپزشکی شناخت, 2019)
Introduction: Gender dysphoria is defined as the sustained desire for or insistence on belonging to the opposite sex as well as considerable discomfort with the assigned gender and gender role. Aim: The present study aimed to examine the role of early maladaptive schemata as cognitive factors, and the role of difficulty in emotion regulation as emotional factors in the emergence of gender dysphoria in transgender men. Method: This is a descriptive correlational study. The statistical population included all men with gender dysphoria, visiting the Iranian Legal Medicine Organization of Razavi Khorasan Province, Iran, from 2014 to 2016, in order to follow legal proceedings for gender reassignment. Fifty participants were selected via convenience sampling, gave informed consent, and completed three questionnaires: the Gratz and Roemer’s Difficulties in Emotion Regulation Scale (DERS), the Young’s Early Maladaptive Schema Questionnaire-Short Form, and the Gender Identity Disorder Questionnaire. Data were analyzed in SPSS using Pearson’s correlation and simultaneous multivariate regression. Results: Based on the regression analysis, the most important variable in emotion regulation was limited access to emotion regulation strategies. Moreover, with regard to early maladaptive schemata, mistrust and emotional inhibition were found to predict gender dysphoria in transsexual men. Conclusion: Results revealed that the simultaneous role of cognitive and emotional factors is significant in the emergence of gender dysphoria in transsexual men.